2007
DOI: 10.1523/jneurosci.3439-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Synapse-Associated Protein-97 Mediates α-Secretase ADAM10 Trafficking and Promotes Its Activity

Abstract: Alzheimer's disease (AD) is a chronic neurodegenerative disorder caused by a combination of events impairing normal neuronal function. Here we found a molecular bridge between key elements of primary and secondary pathogenic events in AD, namely the elements of the amyloid cascade and synaptic dysfunction associated with the glutamatergic system. In fact, we report that synapse-associated protein-97 (SAP97), a protein involved in dynamic trafficking of proteins to the excitatory synapse, is responsible for dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
148
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(161 citation statements)
references
References 54 publications
13
148
0
Order By: Relevance
“…Triton insoluble fraction (TIF), a fraction highly enriched in all categories of postsynaptic density proteins (i.e., receptor, signaling, scaffolding, and cytoskeletal elements) absent of presynaptic markers, and soluble fraction S2, were obtained as previously described (Gardoni et al, 2001;Marcello et al, 2007). In order to avoid protein degradation, AD samples were paired to HC samples and processed at the same time.…”
Section: Triton Insoluble Synaptic Membrane (Tif) and Soluble Fractiomentioning
confidence: 99%
“…Triton insoluble fraction (TIF), a fraction highly enriched in all categories of postsynaptic density proteins (i.e., receptor, signaling, scaffolding, and cytoskeletal elements) absent of presynaptic markers, and soluble fraction S2, were obtained as previously described (Gardoni et al, 2001;Marcello et al, 2007). In order to avoid protein degradation, AD samples were paired to HC samples and processed at the same time.…”
Section: Triton Insoluble Synaptic Membrane (Tif) and Soluble Fractiomentioning
confidence: 99%
“…Marcello et al reported that synapseassociated protein-97, a protein involved in dynamic traffi cking of proteins to the excitatory synapse, drives ADAM10 to the postsynaptic membrane in dendritic spines (Marcello et al , 2007 ). Interestingly, they demonstrated that NMDAR activity directly mediates this event and positively modulates α -secretase activity.…”
Section: Nmdar Activation and Neuronal A β Synthesismentioning
confidence: 99%
“…Moreover, excessive NMDAR activity was shown to contribute importantly to the etiology of many acute or chronic neurodegenerative disorders such as stroke, Hungtinton ' s disease, HIV-associated dementia and AD (Lipton and Rosenberg , 1994 ;Lancelot and Beal , 1998 ). Several studies reported a direct link between NMDAR overactivation on the one hand, and APP processing and neuronal A β secretion on the other hand, even if the conclusions could be somewhat different (Lesn é et al, 2005 ;Marcello et al , 2007 ;Hoey et al , 2009 ). It was further demonstrated that the cellular location of NMDARs is a key parameter controlling their effect on neuronal viability.…”
Section: Introductionmentioning
confidence: 99%
“…Retinoic acid receptors can increase the expression of ADAM10, leading to a decrease in A␤ peptides (Tippmann et al, 2009;Donmez et al, 2010). The activity of ADAM10 is regulated by NMDA receptors (NMDARs), which modulate synaptic trafficking of ADAM10 via synapse-associated protein-97 (SAP97) (Marcello et al, 2007). Interference of the interaction between ADAM10 and SAP97 causes sporadic AD (Epis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%